Pengaruh Variasi Konsentrasi Zn(NO3)2·6H2O Terhadap Gugus Fungsi, Ukuran Partikel, dan Morfologi Partikel Nanopartikel ZnO dengan Metode Sintesis Hijau Menggunakan Ekstrak Daun Kelor - Benyamin, Chairunissa A; Manurung, Posman; Suprihatin, Suprihatin (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
This research was conducted to determine the effect of varying concentrations of Zn(NO3)2·6H2O (zinc nitrate hexahydrate) on functional groups, particle size, and particle morphology of ZnO nanoparticles using the green synthesis method using Moringa leaves. The materials was used in this study were moringa leaf extract, Zn(NO3)2·6H2O with various concentrations of 0.2, 0.4, 0.6, and 0.8 M, and NaOH of 0.1 M. Based on the results of characterization using FTIR, it shows that the functional groups in the content of Moringa leaves play a role in the formation of ZnO nanoparticles. Meanwhile, the results of the XRD characterization showed a diffractogram difference with standard ZnO at concentrations of 0.6 M and 0.8 M Zn(NO3)2·6H2O with the appearance of the NaNO3 phase. SEM characterization results show that the morphology of ZnO nanoparticles using the green synthesis method is irregular in shape.